ChemInform Abstract: Blue‐Emitting K2Al2B2O7:Eu2+ Phosphor with High Thermal Stability and High Color Purity for Near‐UV‐Pumped White Light‐Emitting Diodes. Issue 24 (June 2015) - Xiao, Wenge; Zhang, Xia; Hao, Zhendong; Pan, Guo‐Hui; Luo, Yongshi; Zhang, Ligong; Zhang, Jiahua
Abstract: K2 Al2 B2 O7 :Eu 2+ phosphor is prepared by reaction of a stoichiometric HNO3 solution of Eu2 O3, K2 CO3, Al(NO3 )3, and H3 BO3 followed by drying and sintering in a reducing CO atmosphere (C sticks covered crucible, 1.